2012
DOI: 10.1021/jf301902k
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Oil Enhances Tomato Carotenoid Tissue Accumulation Compared to Safflower Oil in the Mongolian Gerbil (Meriones unguiculatus)

Abstract: Evidence suggests that monounsaturated and polyunsaturated fats facilitate greater absorption of carotenoids than saturated fats. However, the comparison of consuming a polyunsaturated fat source versus a saturated fat source on tomato carotenoid bioaccumulation has not been examined. The goal of this study was to determine the influence of coconut oil and safflower oil on tomato carotenoid tissue accumulation in Mongolian gerbils ( Meriones unguiculatus ) fed a 20% fat diet. Coconut oil feeding increased caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…The amount of β-cryptoxanthin in the spleen seems to be higher than that of other carotenoids. 17,22) We have no clear explanation for the reason that the spleen accumulates β-cryptoxanthin in a high concentration, but we concluded that β-cryptoxanthin may act on the immune system such as production of white blood cell lymphocytes. alternatively, β-cryptoxanthin stored in erythrocytes might be removed from old erythrocyte and accumulated in spleen.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The amount of β-cryptoxanthin in the spleen seems to be higher than that of other carotenoids. 17,22) We have no clear explanation for the reason that the spleen accumulates β-cryptoxanthin in a high concentration, but we concluded that β-cryptoxanthin may act on the immune system such as production of white blood cell lymphocytes. alternatively, β-cryptoxanthin stored in erythrocytes might be removed from old erythrocyte and accumulated in spleen.…”
Section: Resultsmentioning
confidence: 81%
“…dISCUSSION Previously, many studies using animals have focused on the absorption, storage, and tissue distribution of carotenoids, such as β-carotene and/or lycopene. [14][15][16][17][18][19][20][21][22] However, little is known about the bioavailability of β-cryptoxanthin. In this study, we tested the hypothesis that absorbed β-cryptoxanthin is stored in several organs after chronic administration of Satsuma mandarin juice, which is rich in β-cryptoxanthin.…”
Section: Resultsmentioning
confidence: 99%
“…Diet and tissue carotenoid analyses were performed using previously published techniques described by our laboratory [13,19,20]. Briefly, 5 mL of ethanol solution containing 0.01% butylated hydroxytoluene was added to tissue or 25 mg diet, 0.6 g gonadal adipose, or 0.1 g of liver.…”
Section: Diet and Tissue Carotenoid Analysesmentioning
confidence: 99%
“…Diet and tissues were saponified for 30 minutes at 60°C. Samples were extracted 3 times with 6 mL hexane, dried in a Speedvac (model AS160; Savant, Farmingdale, NY, USA) evaporator, flushed with argon, and stored at −20°C for 48 hours or less before reverse-phase HPLC-PDA analysis, as previously described [20]. Analytical standards of lycopene, phytoene, phytofluene, and β-carotene were used for quantification.…”
Section: Diet and Tissue Carotenoid Analysesmentioning
confidence: 99%
“…Skin samples (0.30 g) were frozen with liquid nitrogen, crushed to a fine powder using a Cellcrusher (Cellcrusher Ltd.; Cork, Ireland), and transferred to glass vials. The powdered skin was then suspended in 1 mL of water, spiked with 10 L of the d3-25OHD 3 solution, allowed to equilibrate for 15 min, and extracted for lipophilic compounds as previously described [10,11]. Briefly, 1 mL of ethanol containing 0.1% butylated hydroxytoluene and 5 mL of 5:1 hexane/dichloromethane were added to the skin samples, and the mixture was probe sonicated (Branson Ultrasonics; Danbury, CT) for 30 s. The homogenized solutions were centrifuged at 2000 × g for 5 min, and the upper organic layer was decanted into clean glass vials.…”
Section: Sample Preparationmentioning
confidence: 99%